2010
DOI: 10.1007/s12576-010-0126-7
|View full text |Cite
|
Sign up to set email alerts
|

Vascular adaptations to hypobaric hypoxic training in postmenopausal women

Abstract: The objective of this study was to examine the effects of exercise training in hypoxia on arterial stiffness and flow-mediated vasodilation (FMD) in postmenopausal women. Sixteen postmenopausal women (56±1 years) were assigned to a normoxic exercise group (Normoxic group, n=8) or a hypoxic exercise group (Hypoxic group, n=8). The Hypoxic group performed exercise under hypobaric hypoxic conditions corresponding to 2000 m above sea level, and was exposed to these conditions for 2 h per session. Aquatic exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 75 publications
(114 reference statements)
1
49
0
1
Order By: Relevance
“…5 In addition, Nishiwaki et al reported that hypoxic training increased fl ow-mediated vasodilation (FMD) (an indicator of increased blood fl ow) and reduced PWV, similar to the results of this study. 21 Katayama et al reported that aerobic exercise improved vascular endothelial function to a greater extent in a hypoxic environment than in a sea-level environment.…”
Section: F1 = Difference Between Groups; F2 = Difference Before and Amentioning
confidence: 99%
“…5 In addition, Nishiwaki et al reported that hypoxic training increased fl ow-mediated vasodilation (FMD) (an indicator of increased blood fl ow) and reduced PWV, similar to the results of this study. 21 Katayama et al reported that aerobic exercise improved vascular endothelial function to a greater extent in a hypoxic environment than in a sea-level environment.…”
Section: F1 = Difference Between Groups; F2 = Difference Before and Amentioning
confidence: 99%
“…Rest or exercise under hypoxic conditions decrease body fat mass (Wiesner et al 2010), blood pressure (Schobersberger et al 2003), and arterial stiffness (Vedam et al 2009; Nishiwaki et al 2011) in various populations. Although several effects on metabolic and cardiovascular parameters have been proposed, the beneficial effects of hypoxic stimulation on glucose metabolism are especially attractive.…”
Section: Introductionmentioning
confidence: 99%
“…PWV is generally assessed by measureing the time that the pulse wave takes to travel a given distance along the blood vessel; thus, it is an objective measurement of atherosclerosis. Nishiwaki et al [17] demonstrated a significant increase in the percentage of flow-mediated vasodilation and a significant reduction in PWV after training in the hypoxic group in postmenopausal women. Their results indicate that hypoxic training may induce vascular functional adaptation.…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, new alternatives for traditional altitude training regimes have been proposed, known as "living low and training high", and the effects on endurance performance have been demonstrated extensively in athletes [10][11][12]. Recently, several studies have reported the effects of hypoxia training on physical fitness not only in athletes but also in nonathletes [13][14][15][16][17]. In obese subjects, body weight was significantly decreased in subjects with hypoxia training compared with that in subjects with normoxia training [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation